2018
DOI: 10.3390/polym10030287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Strength Properties of Sand Modified with Organic Polymers

Abstract: Due to weak physical properties of sand, chemical reinforcement methods are widely used to improve sand properties to meet the engineering requirements. However, most of the traditional additives cause environmental problems. Therefore, non-traditional additives such as liquid polymers, enzymes, ions, and lignin derivatives have been studied extensively. In this study, organic polymer is used as a soil stabilizer to reinforce the sand. To evaluate the effectiveness of the organic polymer as soil stabilizer, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…They reported that the compressive strength after the application was 161-600 psi, while the permeability to original was 80% at 60 • C, [100]. Liu et al [24,101] used poly-oxypropylene diol, poly-oxyethylene glycol, poly-caprolaclone glycol, and toluene to consolidate an unconsolidated sand formation, Table 19. They disclosed that the shear strength cohesion values for 50% polymer with densities of 1.40, 1.50 and 1.60 g/cm 2 were 120.19, 140.28, and 204.22 kPa respectively, [24,101].…”
Section: Polyurethane Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the compressive strength after the application was 161-600 psi, while the permeability to original was 80% at 60 • C, [100]. Liu et al [24,101] used poly-oxypropylene diol, poly-oxyethylene glycol, poly-caprolaclone glycol, and toluene to consolidate an unconsolidated sand formation, Table 19. They disclosed that the shear strength cohesion values for 50% polymer with densities of 1.40, 1.50 and 1.60 g/cm 2 were 120.19, 140.28, and 204.22 kPa respectively, [24,101].…”
Section: Polyurethane Resinsmentioning
confidence: 99%
“…Liu et al [24,101] used poly-oxypropylene diol, poly-oxyethylene glycol, poly-caprolaclone glycol, and toluene to consolidate an unconsolidated sand formation, Table 19. They disclosed that the shear strength cohesion values for 50% polymer with densities of 1.40, 1.50 and 1.60 g/cm 2 were 120.19, 140.28, and 204.22 kPa respectively, [24,101]. Some pros and cons of polyurethane resins methods, as reported in the literature and summarized in Table 20.…”
Section: Polyurethane Resinsmentioning
confidence: 99%
“…The constitutional formula of PU used in this study is shown in Figure 1(a), which was synthetized based on five main stages including atmospheric distillation, vacuum distillation, cooling, heating, and cooling, as shown in Figure 1(b). This synthesis method follows Liu [29] and Liu et al [30].…”
Section: Laboratory Chemical Synthesis Of Polyurethane (Pu)mentioning
confidence: 99%
“…The concentrations of the polymer were 0%, 10%, 20% and 30% (S9, S10, S11 and S12) in the test. After the specimen preparation, the specimens were cured at 20 • C for 24 h. In the test, the YYW-2 unconfined compressional strain control device (Nanjing Nantu Instrument Equipment Co. Ltd., Nanjing, China) was used, and the controlling strain rate was 2.4 mm/min [27]. The test was based on the ASTM standard (ASTM D2166-00).…”
Section: Unconfined Compression Testmentioning
confidence: 99%